2022
DOI: 10.3389/fcimb.2022.976843
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of host miRNAs in the flavivirus 3´UTR genome: From bioinformatics predictions to practical approaches

Abstract: The genus Flavivirus of the Flaviviridae family includes important viruses, such as Dengue, Zika, West Nile, Japanese encephalitis, Murray Valley encephalitis, tick-borne encephalitis, Yellow fever, Saint Louis encephalitis, and Usutu viruses. They are transmitted by mosquitoes or ticks, and they can infect humans, causing fever, encephalitis, or haemorrhagic fever. The treatment resources for these diseases and the number of vaccines available are limited. It has been discovered that eukaryotic cells synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 131 publications
0
1
0
Order By: Relevance
“…As reported, JMTV retained the 5′-CAAGUG-3′ sequence in the UTR of all the segments during its first isolation, which indicated that all four segments belonged to the same virus [ 2 ]. The conserved location of the 5′-CAAGUG-3′ sequence in the first structures of the untranslated regions may indicate that this region is involved in interactions with viral and/or cellular proteins to regulate the virus’s life cycle, similarly to how it occurs in other viruses of the Orthoflavivirus genus [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, JMTV retained the 5′-CAAGUG-3′ sequence in the UTR of all the segments during its first isolation, which indicated that all four segments belonged to the same virus [ 2 ]. The conserved location of the 5′-CAAGUG-3′ sequence in the first structures of the untranslated regions may indicate that this region is involved in interactions with viral and/or cellular proteins to regulate the virus’s life cycle, similarly to how it occurs in other viruses of the Orthoflavivirus genus [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This new type of vaccines can induce neutralizing antibody production in mice [268] and could be a promising strategy to avoid the antibody-dependent enhancement (ADE) phenomenon, which causes increased viral replication due to the production of specific antibodies against viruses that facilitates viral entry, upregulates autophagy, and inhibits interferon signaling. For some viruses, the ADE phenomenon is not abolished with MREbased vaccines, but this question could be overcome by proposing miRNAs not as a viral genome modification, but as an active compound of a drug used as prevention or therapeutic treatment, as shown in a recent review [269].…”
Section: Artificial Micrornasmentioning
confidence: 99%